Secondary battery

By using single-particle lithium-nickel active materials with high nickel content and LCO, LMO and LFP in the form of secondary particles in the cathode active material layer of the secondary battery, the problem of rapid increase in the negative electrode resistance of the secondary battery is solved and the battery is realized Improved lifespan and room temperature cycle characteristics.

CN119365998APending Publication Date: 2025-01-24LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380046765.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-25
Filing Date
2023-09-26
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The resistance of the negative electrode of the secondary battery increases rapidly at the end of discharge, resulting in a shortening of battery life and deterioration of room temperature cycle characteristics.

Method used

The positive electrode active material layer contains a lithium nickel active material in the form of single particles and one or more of LCO (LiCoO2), LMO (LiMn2O4) and LFP (LiFePO4) in the form of secondary particles, and relative to 100 mol% of the For metals other than lithium, lithium-nickel active materials in the form of single particles contain more than 55 mol% of nickel.

Benefits of technology

The end of the positive resistance at the end of the discharge is reduced rapidly, and the difference between the resistance of the negative electrode and the resistor of the positive electrode is reduced, thereby improving the life of the battery and room temperature circulation characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005184899030000141
    Figure BDA0005184899030000141
  • Figure BDA0005184899030000151
    Figure BDA0005184899030000151
Patent Text Reader

Abstract

The present invention provides a secondary battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, in which the negative electrode comprises a silicon-based active material and a carbon-based active material, in which the positive electrode comprises a lithium nickel-based active material in a single particle form and one or more of LCO (LiCoO2), LMO (LiMn2O4), and LFP (LiFePO4) in a secondary particle form, and in which the lithium nickel-based active material is separated from the lithium nickel-based active material. The lithium nickel-based active material in the form of a single particle contains 55 mol% or more of nickel with respect to 100 mol% of a metal other than lithium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of Korean Patent Application No. 10-2022-0132117 filed on October 14, 2022, in the Korean Intellectual Property Office and Korean Patent Application No. 10-2023-0127952 filed on September 25, 2023, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a secondary battery. Background Art

[0003] Secondary batteries are commonly used not only in portable devices but also in electric vehicles (EV) or hybrid electric vehicles (HEV) driven by an electric drive source due to their easy application to various products and electrical characteristics such as high energy density.

[0004] Secondary batteries have attracted attention as a new energy source that improves eco-friendliness and energy efficiency due to a primary advantage of significantly reducing the use of fossil fuels and a secondary advantage of using energy without generating byproducts.

[0005] Generally, a secondary battery includes a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, an electrolyte, etc. In addition, the positive electrode and the negative electrode may be formed on a current collector, and the current collector has active material layers each containing a positive electrode active material and a negative electrode active material. Generally, for the positive electrode, a lithium-containing metal oxide (e.g., LiCoO 2 and LiMn 2 O 4 ) is used as the positive electrode active material, and for the negative electrode, a carbon-based compound, a silicon-based compound or a mixture thereof, etc. is used as the negative electrode active material.

[0006] Recently, in order to develop a battery capable of rapid charging, a mixture of a carbon compound (e.g., graphite) and a silicon compound is used for the negative electrode. However, when a silicon compound is included, the resistance of the negative electrode increases rapidly at the end of discharge, resulting in an increase in the difference between the resistance of the negative electrode and the resistance of the positive electrode, which shortens the life of the battery and deteriorates the room temperature cycle characteristics. Therefore, it is necessary to develop a battery to solve these problems.

[0007] Prior art literature

[0008] [Patent Document]

[0009] (Patent Document 1) Korean Patent Application Publication No. 10-2012-0037409 Summary of the invention

[0010] [Technical issues]

[0011] The present invention is directed to providing a secondary battery having improved lifespan and room temperature cycle characteristics by reducing the difference between the resistance of a negative electrode and the resistance of a positive electrode at the end of discharge by including a silicon-based compound in a negative electrode active material layer.

[0012] However, the technical problems to be solved by the present invention are not limited to the above problems, and those skilled in the art can clearly understand other problems not described from the following description.

[0013] [Technical solution]

[0014] An exemplary embodiment of the present invention provides a secondary battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode comprises a silicon-based active material and a carbon-based active material, wherein the positive electrode comprises: a lithium-nickel-based active material in the form of a single particle; and LCO (LiCoO 2 )、LMO(LiMn 2 O 4 ) and LFP (LiFePO 4 ) and wherein the lithium nickel-based active material in the form of a single particle contains 55 mol % or more of nickel relative to 100 mol % of metal other than lithium.

[0015] [Beneficial Effects]

[0016] The secondary battery of the present invention comprises a lithium nickel-based active material in the form of a single particle and LCO (LiCoO) in the form of a secondary particle in the positive electrode active material layer. 2 )、LMO(LiMn 2 O 4 ) and LFP (LiFePO 4 ) in one or more, thereby being able to reduce the rapid decrease in the resistance of the positive electrode at the end of discharge. Therefore, a secondary battery can be obtained that reduces the difference between the resistance of the negative electrode and the resistance of the positive electrode and has improved life and room temperature cycle characteristics.

[0017] Specifically, a lithium nickel-based active material in the form of a single particle with a high nickel content is used for the positive electrode active material layer to increase the energy density of the battery and reduce the breakage of the active material, and a silicon-based active material is included in the negative electrode active material layer to enable rapid charging. At this time, the resistance of the negative electrode increases rapidly at the end of discharge, resulting in a large difference between the resistance of the positive electrode and the resistance of the negative electrode, which leads to an excessive increase in the use of the silicon-based active material contained in the negative electrode active material layer (increased depth of use) and deterioration of the life performance of the battery. In order to improve the above problems, a lithium nickel-based active material in the form of a single particle and LCO (LiCoO 2 )、LMO(LiMn 2 O 4) and LFP (LiFePO 4 ) in order to enable fast charging, improve the resistance of the positive electrode, and reduce the resistance difference between the positive electrode and the negative electrode and the depth of use of the silicon-based active material, thereby obtaining a secondary battery with improved room temperature life. DETAILED DESCRIPTION

[0018] Hereinafter, the present invention will be described in detail. The following description is intended to help understand the present invention, but does not determine or limit the scope of the present invention.

[0019] In the present specification, when a part is referred to as “including / comprising” a certain component, this means that the part may further include / comprising another component, without excluding the other component, unless specifically described otherwise.

[0020] Throughout the specification, when an element is referred to as being 'on' another element, the element may be in direct contact with the other element, or intervening elements may also be present.

[0021] It should be understood that the terms or words used throughout the specification should not be interpreted as limited to their general meanings or dictionary meanings, but are interpreted as having meanings and concepts consistent with the technical ideas of the present invention based on the concept that the inventor can appropriately define the words or terms to best explain the principle of the present invention.

[0022] As used herein, the singular forms “a”, “an” and “the” are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0023] In the present specification, the crystallinity of the structure contained in the positive electrode or negative electrode active material can be confirmed by X-ray diffraction analysis, and the X-ray diffraction analysis can be performed by using an X-ray diffraction (XRD) analyzer (product name: D4-Endavor, manufacturer: Bruker), or, in addition to the above-mentioned equipment, equipment used in the prior art can also be used.

[0024] In the present specification, the presence or absence of an element in the positive electrode or negative electrode active material and the content of the element can be confirmed by ICP analysis, and the ICP analysis can be performed by using an inductively coupled plasma atomic emission spectrometer (ICP AES, Perkin-Elmer 7300).

[0025] In this specification, the end of discharge refers to a period in which the SOC (state of charge) of all cells is 10% or less.

[0026] In this specification, the average particle size (D 50 The average particle size (D) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. 50) can be measured using laser diffraction. For example, the average particle size (D 50 ) may include dispersing particles of the positive electrode active material in a dispersion medium, introducing the dispersion into a commercially available laser diffraction particle size measuring device (e.g., HORIBALA-960), irradiating the dispersion with ultrasonic waves of about 28 kHz at an output of 60 W, and then calculating the average particle size (D ) corresponding to 50% of the cumulative volume in the measuring device. 50 ).

[0027] In this specification, the term "single particle" is a concept opposite to the form of secondary particles formed by agglomeration of tens to hundreds of primary particles, and refers to a particle composed of 10 or less primary particles. Specifically, in the present invention, a single particle may be a single particle composed of one primary particle, or may be a particle form formed by agglomeration of several primary particles.

[0028] In this specification, the term "primary particle" refers to the smallest unit of a particle recognized when an active material is observed by a scanning electron microscope, and "secondary particle" refers to a secondary structure formed by agglomeration of tens to hundreds of primary particles.

[0029] In this specification, the expression "particle" refers to micron-sized particles, and when observed under magnification, the particles can be identified as "grains" having a crystal form with a size of tens of nanometers. When the grains are further magnified, a separate region in the form of atoms forming a lattice structure in a predetermined direction can be identified, wherein the region is referred to as a "crystal". The size of the particles observed by X-ray diffraction (XRD) is defined as the size of the crystallite. The size of the crystallite can be quantitatively determined by the Scherrer equation using XRD data.

[0030] The secondary battery of the present invention comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode comprises a silicon-based active material and a carbon-based active material, and the positive electrode comprises a lithium-nickel-based active material in the form of a single particle and LCO (LiCoO 2 )、LMO(LiMn 2 O 4 ) and LFP (LiFePO 4 ) and wherein the lithium nickel-based active material in the form of a single particle contains 55 mol % or more of nickel relative to 100 mol % of metal other than lithium.

[0031] In this specification, when the negative electrode active material layer contains a silicon-based active material, the resistance of the negative electrode increases rapidly at the end of discharge, and the resistance of the positive electrode using a positive electrode material having a low resistance characteristic decreases rapidly, so the difference between the resistance of the negative electrode and the resistance of the positive electrode increases significantly. Therefore, there is a problem that the degradation of the negative electrode progresses rapidly, shortening the life of the battery and deteriorating the room temperature cycle characteristics. In order to solve this problem, a lithium nickel-based active material in the form of a single particle and LCO (LiCoO 2 )、LMO(LiMn 2 O 4 ) and LFP (LiFePO 4 ) to reduce the rapid decrease in resistance of the positive electrode, thereby obtaining a battery with improved life and room temperature cycle characteristics.

[0032] <Cathode Materials>

[0033] The positive electrode of the present invention comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises: a lithium nickel-based active material in the form of a single particle, and LCO (LiCoO 2 )、LMO(LiMn 2 O 4 ) and LFP (LiFePO 4 ). In this case, the lithium nickel-based active material in the form of a single particle contains 55 mol% or more of nickel, specifically 55 mol% or more and less than 80 mol% of nickel, or 80 mol% or more of nickel, relative to 100 mol% of metal other than lithium. The present invention includes LCO (LiCoO 2 )、LMO(LiMn 2 O 4 ) and LFP (LiFePO 4 ) and mixed with a lithium nickel-based active material to have the effect of reducing the positive electrode voltage at the end of discharge.

[0034] According to an exemplary embodiment of the present invention, the positive electrode includes a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes: a lithium nickel-based active material in the form of a single particle; and LCO (LiCoO 2 )、LMO(LiMn 2 O 4 ) and LFP (LiFePO 4 )

[0035] According to an exemplary embodiment of the present invention, the positive electrode active material layer includes a lithium nickel-based active material in the form of a single particle and LCO (LiCoO 2).

[0036] According to an exemplary embodiment of the present invention, the positive electrode active material layer includes a lithium nickel-based active material in the form of a single particle and LMO (LiMn 2 O 4 ).

[0037] According to an exemplary embodiment of the present invention, the positive electrode active material layer includes a lithium nickel-based active material in the form of a single particle and LFP (LiFePO 4 ).

[0038] According to an exemplary embodiment of the present invention, the positive electrode active material layer includes a lithium nickel-based active material in the form of a single particle and LMO (LiMn 2 O 4 ) and LFP (LiFePO 4 )

[0039] In an exemplary embodiment of the present invention, the LCO (LiCoO) in the form of secondary particles is 100 parts by weight of the total amount of the positive electrode active material of the positive electrode active material layer. 2 )、LMO(LiMn 2 O 4 ) and LFP (LiFePO 4 ) is 0.1 to 10 parts by weight, specifically 0.1 to 5 parts by weight, or 0.1 to 3 parts by weight. In this case, the total amount of the positive electrode active material may refer to a lithium nickel-based active material in a single particle form, or a lithium nickel-based active material in a single particle form and an additional active material. When LCO (LiCoO 2 )、LMO(LiMn 2 O 4 ) and LFP (LiFePO 4 ) satisfies the above range, the negative electrode potential increase caused by the decrease in the positive electrode voltage at the end of discharge is suppressed, thereby showing the effect of suppressing negative electrode degradation. In addition, since LCO (LiCoO 2 )、LMO(LiMn 2 O 4 ) and LFP (LiFePO 4 ) have a charge / discharge capacity (mAh) / g lower than that of lithium nickel active materials. If LCO (LiCoO 2 )、LMO(LiMn 2 O 4 ) and LFP (LiFePO 4) If the content of one or more of them exceeds the above range, the battery capacity may decrease.

[0040] According to an exemplary embodiment of the present invention, the average particle size (D 50 ) of the lithium nickel-based active material in the form of single particles is 3 μm to 10 μm.

[0041] The lithium nickel-based active material of the present invention may include a lithium composite metal oxide containing nickel, lithium, and one or more metals such as cobalt, manganese, or aluminum. More specifically, lithium nickel manganese cobalt-based oxides (for example

[0042] Li(Ni p Co q Mn r1 )O 2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1, p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O 4 (in

[0043] this case, 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2), etc.), lithium nickel cobalt transition metal (M) oxides (for example Li(Ni) p2 Co q2 Mn r3 M S2 )O 2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r3, and s2 are each independently the atomic fraction of the element, 0 < p2 < 1, 0 < q2 < 1, 0 ≤ r3 < 1, 0 < s2 < 1, p2 + q2 + r3 + s2 = 1), etc.), and may include any one or two or more of these compounds.

[0044] However, the present invention is not limited thereto.

[0045] In addition to the above positive electrode active material layer, the positive electrode may further include a positive electrode current collector. In this case, the positive electrode active material layer is formed on at least one surface of the positive electrode current collector.

[0046] In the positive electrode, the positive electrode current collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., etc. can be used. In addition, the thickness of the positive electrode current collector can generally be 3 μm to 500 μm, and the surface of the current collector can be formed with microscopic concave-convex objects to enhance the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0047] The positive electrode active material layer may include a positive electrode conductive material and a positive electrode binder together with the above-mentioned positive electrode active material.

[0048] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the battery to be constituted. Specific examples may include: graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and any one of them or a mixture of two or more thereof may be used.

[0049] In addition, the positive electrode binder is used to improve the adhesion between the particles of the positive electrode active material and the adhesion between the positive electrode active material and the positive electrode current collector. Specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one or a mixture of two or more thereof may be used.

[0050] The positive electrode active material layer can be formed by: forming a lithium nickel-based active material in the form of a single particle, LCO (LiCoO 2 )、LMO(LiMn 2 O 4 ) and LFP (LiFePO 4 ) and a positive electrode slurry of one or more of the foregoing materials and a binder and / or a conductive material is applied to at least one surface of a positive electrode current collector, and then the slurry is dried and roll-pressed.

[0051] The positive electrode slurry according to the exemplary embodiment of the present invention may further include a solvent for forming the positive electrode slurry. Specifically, the solvent for forming the positive electrode slurry may include methyl pyrrolidone (NMP) or the like to facilitate dispersion of the components.

[0052] In an exemplary embodiment of the present invention, the solid content of the positive electrode slurry may be 20 to 85 parts by weight, specifically 30 to 80 parts by weight, based on 100 parts by weight of the total amount of the positive electrode slurry.

[0053] According to an exemplary embodiment of the present invention, the porosity of the positive electrode is 19% to 23%.

[0054] The porosity can be calculated as: (1-(rolling density / true density of electrode))*100(%).

[0055] The roll density can be calculated as follows.

[0056] Rolling density: The weight of the electrode excluding the foil after rolling the electrode (g) / the volume of the electrode excluding the foil (sample area * electrode layer thickness, cm 3 )

[0057] The volume of the electrode excluding the foil refers to the total volume including the pores in the electrode, and is calculated as the product of the unit area of ​​the sample and the thickness of the electrode layer after rolling.

[0058] The true density of an electrode is the intrinsic density of an electrode active material and refers to the density of a portion filled only with material except for the gaps between particles. The true density of an electrode is measured by applying Archimedes' principle to calculate a density value by measuring the volume (solid + isolated pores) other than open pores, or by using a gas densimeter.

[0059] <Negative electrode>

[0060] The negative electrode according to the exemplary embodiment of the present invention includes a negative electrode active material layer, and the negative electrode active material layer includes a silicon-based active material and a carbon-based active material.

[0061] According to an exemplary embodiment of the present invention, the negative electrode includes a negative electrode active material layer, and the negative electrode active material layer includes a silicon-based active material and a carbon-based active material.

[0062] In addition to the above-mentioned negative electrode active material layer, the negative electrode may also include a negative electrode current collector. In this case, the negative electrode active material layer is formed on at least one surface of the negative electrode current collector. The negative electrode active material layer includes a silicon-based active material and a carbon-based active material. In addition, the negative electrode active material layer may also include a binder and / or a conductive material.

[0063] According to an exemplary embodiment of the present invention, carbonaceous active materials can be used without particular limitation, and representative examples thereof may include crystalline carbon, amorphous carbon, or a combination thereof. Examples of crystalline carbon may include graphite, such as natural graphite and artificial graphite in amorphous, plate-like, flaky, spherical, or fibrous forms, and examples of amorphous carbon may include soft carbon (low-temperature sintered carbon), hard carbon, mesophase pitch carbide, sintered coke, and the like. The graphite may be natural graphite, artificial graphite, or a mixture thereof. The content of the carbonaceous active material may be 60 parts by weight or more and 99 parts by weight or less relative to the total amount of the negative electrode active material contained in 100 parts by weight of the negative electrode active material layer.

[0064] According to an exemplary embodiment, the negative electrode includes a silicon-based active material.

[0065] Containing SiO x (0 < x < 2) As the active material of the silicon-based active material, it may be silicon-based composite particles containing SiO x (0 < x < 2) and pores.

[0066] SiO x (0 < x < 2) corresponds to the matrix in the silicon-based composite particles. SiO x (0 < x < 2) may be in a form containing Si and SiO 2 , and Si may form a phase. That is, x corresponds to the ratio of the number of O to Si contained in SiO x (0 < x < 2). When the silicon-based composite particles contain SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.

[0067] The silicon-based composite particles may further include at least one of a Mg compound and a Li compound. The Mg compound and the Li compound may correspond to the matrix in the silicon-based composite particles.

[0068] The Mg compound and / or the Li compound may be present in SiO x (0 < x < 2) and / or on the surface of SiO x (0 < x < 2). Through the Mg compound and / or the Li compound, the initial efficiency of the battery can be improved.

[0069] The Mg compound may include at least one selected from the group consisting of Mg silicate, Mg silicide, and Mg oxide. The Mg silicate may include Mg 2 SiO 4 or MgSiO 3 or at least one of them. The Mg silicide may include Mg 2 Si. The Mg oxide may include MgO.

[0070] In an exemplary embodiment of the present specification, based on the total amount of the silicon-based active material of 100% by weight, the content of the Mg element may be from 0.1% by weight to 20% by weight, or from 0.1% by weight to 10% by weight. Specifically, the content of the Mg element may be from 0.5% by weight to 8% by weight, or from 0.8% by weight to 4% by weight. When the above ranges are satisfied, the Mg compound can be included in the silicon-based active material in an appropriate content, so that the volume change of the silicon-based active material during battery charging and discharging can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0071] The Li compound may include at least one selected from the group consisting of Li silicate, Li silicide, and Li oxide. The Li silicate may include Li 2 SiO 3 、Li 4 SiO 4 and Li 2 Si 2 O 5 at least one of. The Li silicide may include Li 7 Si 2 . The Li oxide may include Li 2 O.

[0072] In an exemplary embodiment of the present invention, the Li compound may be included in the form of lithium silicate. The lithium silicate is represented as Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and can be divided into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate may exist in the silicon-based composite particles in the form of at least one lithium silicate selected from the group consisting of Li 2 SiO 3 、Li 4 SiO 4 and Li 2 Si 2 O 5 at least one of the lithium silicates, and the amorphous lithium silicate may be in the form of Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5). However, the present invention is not limited thereto.

[0073] In the exemplary embodiment of the present specification, the content of the Li element may be 0.1 wt % to 20 wt %, or 0.1 wt % to 10 wt %, based on 100 wt % of the total amount of the silicon-based active material. Specifically, the content of the Li element may be 0.5 wt % to 8 wt %, more specifically 0.5 wt % to 4 wt %. When the above range is satisfied, the Li compound may be included in the silicon-based active material at a suitable content, so that the volume change of the negative electrode active material during battery charging and discharging can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0074] The content of Mg element or Li element can be confirmed by ICP analysis. For ICP analysis, a predetermined amount (about 0.01g) of negative electrode active material is accurately taken, transferred to a platinum crucible, and completely decomposed on a heating plate by adding nitric acid, hydrofluoric acid and sulfuric acid thereto. Then, an inductively coupled plasma atomic emission spectrometer (ICP-AES, Perkin-Elmer7300) is used to measure the intensity of a standard solution prepared using a standard solution (5mg / kg) at the inherent wavelength of the Mg element or Li element to obtain a reference calibration curve. Subsequently, the pretreated sample solution and the blank sample are introduced into the spectrometer, and the actual intensity is calculated by measuring the intensity of each component, and the concentration of each component is calculated based on the obtained calibration curve, and then converted so that the sum of the calculated component concentrations is equal to the theoretical value, thereby analyzing the Mg element or Li element content in the prepared silicon-based active material.

[0075] In an exemplary embodiment of the present specification, a carbon layer may be provided on the surface and / or in the pores of the silicon-based composite particles. The carbon layer imparts conductivity to the silicon-based composite particles, thereby improving the initial efficiency, life characteristics, and battery capacity characteristics of a secondary battery containing a negative electrode active material containing the silicon-based composite particles. Based on 100% by weight of the total amount of the silicon-based composite particles, the total amount of the carbon layer included may be 5% by weight to 40% by weight.

[0076] In the exemplary embodiment of the present specification, the carbon layer may include at least one of amorphous carbon or crystalline carbon.

[0077] In an exemplary embodiment of the present invention, the silicon-based active material may be SiO β (0<β<2) or Si-C complex.

[0078] The average particle size of silicon active materials (D 50 ) may be 2 μm to 15 μm, specifically 3 μm to 12 μm, and more specifically 4 μm to 10 μm. When the above range is met, the side reaction between the silicon-based composite particles and the electrolyte solution is controlled, and the discharge capacity and initial efficiency of the battery can be effectively achieved.

[0079] In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. 50 ) can be measured using, for example, the laser diffraction method. In the laser diffraction method, particle sizes from submicrometers to several millimeters can generally be measured, and results with high reproducibility and high resolution can be obtained.

[0080] In addition, in an exemplary embodiment of the present invention, the content of the silicon-based active material is 1 to 15 parts by weight, preferably 1 to 10 parts by weight, and more preferably 5 to 10 parts by weight, relative to 100 parts by weight of the total amount of the negative electrode active material. In this case, the total amount of the negative electrode active material may refer to a silicon-based active material and a carbon-based active material; or a silicon-based active material, a carbon-based active material, and an additional active material. When the content of the silicon-based active material satisfies the above range, an improved effect is obtained in terms of energy density and cell resistance, and an excellent effect is obtained in terms of life because the volume expansion occurring during the charge / discharge process is small.

[0081] According to the exemplary embodiment of the present specification, the negative electrode slurry may further include an additional negative electrode active material in addition to the above-mentioned silicon-based active material.

[0082] As an additional negative electrode active material, a compound capable of reversibly inserting and deinserting lithium may be used. Specific examples may include metal materials capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; metal oxides capable of doping and dedoping lithium, such as SiO β (0<β<2), SnO 2 , vanadium oxide, lithium titanium oxide and lithium vanadium oxide; a composite material containing a metal material and a carbon material, such as a Si-C composite or a SnC composite; a carbon active material, etc., and any one of them or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material.

[0083] In an exemplary embodiment of the present invention, a weight ratio of the silicon-based active material contained in the negative electrode slurry to the additional negative electrode active material may be 1:99 to 90:10, specifically 1:99 to 50:50.

[0084] The negative electrode current collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery. For example, for the current collector, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, aluminum or stainless steel each surface-treated with carbon, nickel, titanium, silver, etc., etc. can be used. Specifically, transition metals (such as copper and nickel) that adsorb carbon well can be used for the current collector. The thickness of the current collector can be 6 μm to 20 μm. However, the thickness of the current collector is not limited thereto.

[0085] The adhesive may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, and the above materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.

[0086] There is no particular limitation on the conductive material as long as it has conductivity and does not cause chemical changes in the battery. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; fluorocarbon powders; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.

[0087] The negative electrode slurry may further include a thickener such as sodium carboxymethyl cellulose (Na-CMC), lithium carboxymethyl cellulose (Li-CMC), and cellulose nanofibers (CNF).

[0088] The negative electrode slurry of the exemplary embodiment of the present invention may further include a negative electrode slurry forming solvent. Specifically, the negative electrode slurry forming solvent may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropanol, and may include distilled water in terms of promoting dispersion of components.

[0089] In an exemplary embodiment of the present invention, the solid content of the negative electrode slurry may be 20 to 75 parts by weight, specifically 30 to 70 parts by weight, based on 100 parts by weight of the total amount of the negative electrode slurry.

[0090] <Secondary Battery>

[0091] The secondary battery of the exemplary embodiment of the present invention may include a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode and the negative electrode have been described above, a detailed description is omitted.

[0092] The separator is used to separate the negative electrode from the positive electrode, and to provide a migration path for lithium ions, wherein any separator can be used as the separator without particular limitation, as long as it is commonly used for secondary batteries, and in particular, it is preferred to use a separator having a high water retention capacity for the electrolyte solution and a low resistance to the migration of electrolyte ions. Specifically, a porous polymer film can be used, such as a porous polymer film made of a polyolefin polymer (such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer), or a laminated structure having two or more layers thereof can be used. In addition, conventional porous nonwoven fabrics can be used, such as nonwoven fabrics formed by high melting point glass fibers, polyethylene terephthalate fibers, etc. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be selectively used.

[0093] Examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that may be used to manufacture a lithium secondary battery, but are not limited thereto.

[0094] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0095] As the non-aqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate or ethyl propionate can be used.

[0096] Especially, in carbonate organic solvent, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents, and can be preferably used because they have high dielectric constant to dissociate lithium salt well.When cyclic carbonate is mixed with linear carbonate (such as dimethyl carbonate and diethyl carbonate) with low viscosity and low dielectric constant in a suitable ratio and used, it is possible to prepare an electrolyte with high conductivity, so it is possible to be more preferably used.

[0097] A lithium salt can be used as the metal salt, and the lithium salt is a material that is easily soluble in a non-aqueous electrolyte solution, among which, for example, a material selected from F - , Cl - ,I - 、NO 3 - 、N(CN) 2 - , BF 4 - , ClO 4 - PF 6 - ,(CF 3 ) 2 PF 4 - ,(CF 3 ) 3 PF 3 - ,(CF 3 ) 4 PF 2 - ,(CF 3 ) 5 PF - ,(CF 3 ) 6 P - CF 3 SO 3 - CF 3 CF 2 SO 3 - ,(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - CF 3 CF 2 (CF 3 ) 2 CO - ,(CF 3 SO 2 ) 2 CH - , (SF 5 ) 3 C - ,(CF 3 SO 2 ) 3 C - CF 3 (CF2 ) 7 SO 3 - CF 3 CO 2 - , CH 3 CO 2 - 、SCN - and (CF 3 CF 2 SO 2 ) 2 N - One or more species of the group consisting of are used as anions of the lithium salt.

[0098] In addition to the above-mentioned electrolyte components, the electrolyte may also contain one or more additives, for example, halogenated alkylene carbonate compounds (such as difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glycol dimethyl ether, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, to improve the life characteristics of the battery, inhibit the capacity reduction of the battery, improve the discharge capacity of the battery, etc.

[0099] Another exemplary embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries having high capacity and high life and cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0100] Embodiments of the present invention

[0101] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are provided only to illustrate the present invention, and various modifications and changes can be made within the scope of the present invention and technical ideas. These modifications and changes naturally fall within the scope of the claims attached hereto.

[0102] <Example 1>

[0103] <Preparation Example>

[0104] <Preparation of lithium secondary battery>

[0105] Preparation of positive electrode

[0106] As the positive electrode active material, single-particle LiNi 0.86Co 0.05 Mn 0.08 Al 0.01 O 2 (Ni: 86 mol% relative to 100 mol% of metals other than lithium, average particle size (D 50 ): 4 μm) and secondary particle form of LFP (LiFePO 4 ), and relative to 100 parts by weight of the total amount of the positive electrode active material of the positive electrode active material layer, LFP (LiFePO 4 ) was 3 parts by weight. A positive electrode slurry was prepared by adding a positive electrode active material, a binder, and a conductive material to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry at a weight ratio of 97:1.8:1.2.

[0107] The binder is polyvinylidene fluoride (PVDF) and the conductive material is carbon nanotubes (CNT).

[0108] The positive electrode slurry was heated to 3.92 mAh / cm 2 An electrode loading of 500 Å was coated on both surfaces of an aluminum current collector (thickness: 12 μm) serving as a positive electrode current collector, roll-pressed, and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer, thereby preparing a positive electrode.

[0109] Preparation of negative electrode

[0110] A negative electrode slurry was prepared by adding artificial graphite, natural graphite (the weight ratio of artificial graphite to natural graphite was 8:2, excluding the SiO ratio) and SiO (the content was 6 parts by weight relative to 100 parts by weight of the negative electrode active material) as negative electrode active materials, a binder, carboxymethyl cellulose (CMC) and a conductive material in a weight ratio of 95.573:2.3:1.127:1 to distilled water as a solvent for forming a negative electrode slurry.

[0111] The binder is styrene-butadiene rubber (SBR) and the conductive material is carbon nanotubes (CNT).

[0112] The negative electrode slurry was heated to 4.10 mAh / cm 2 An electrode loading of 500 Å was coated on both surfaces of a copper current collector (thickness: 6 μm) serving as a negative electrode current collector, roll-pressed, and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer.

[0113] Preparation of lithium secondary batteries

[0114] A lithium secondary battery was prepared by using the above-mentioned positive electrode and negative electrode, using a multilayer polyethylene / polypropylene / polyethylene separator (thickness: 14 μm) as a separator, and injecting a non-aqueous organic solvent containing a lithium salt as an electrolyte (N / P ratio: 104.7%, weight of the finished battery cell: 502.0 g, thickness of the finished battery cell: 8.24 mm).

[0115] <Examples 1 to 6 and Comparative Examples 1 to 5>

[0116] A lithium secondary battery was prepared in the same manner as in Example 1, except that only the type and composition of the positive electrode active material or the added compound were different from those in Example 1, as shown in Table 1 below.

[0117] [Table 1]

[0118]

[0119] Using different positive active materials of Examples 1 to 6 and Comparative Examples 1 to 5, the capacity retention rate and resistance increase rate of the battery were measured as a result of 100 cycles of room temperature life in situ, and the results are shown in Table 2 below.

[0120] [Table 12]

[0121]

[0122] From the results of Examples 1 to 6 in Table 1, it can be confirmed that when LCO (LiCoO 2 )、LMO(LiMn 2 O 4 ) and LFP (LiFePO 4 ) is added to a lithium nickel-based active material containing 55 mol % or more of nickel relative to 100 mol % of metal other than lithium, the positive electrode potential drops rapidly at the end of discharge to suppress the increase in the negative electrode potential, so that the resistance increase rate of the negative electrode is reduced, and the capacity retention rate is excellent. As shown in Table 1 above, Comparative Example 1 corresponds to a lithium nickel-based active material containing only LiNi 0.86 Co 0.05 Mn 0.08 Al 0.01 O 2 (Ni: 86 mol% relative to 100 mol% of metals other than lithium, average particle size (D 50 ):4μm) as the positive electrode active material. In this case, LFP (LiFePO 4 ) compared to the positive electrode, the resistance increase rate of the negative electrode increased by about 25%, the usage depth of the negative electrode increased, and through the capacity retention rate evaluation, it can be confirmed that the capacity retention rate decreased by about 10% after 100 cycles.

[0123] Comparative Examples 2 and 3 correspond to the positive electrode active material comprising LFP (LiFePO 4 ), but the weight ratio relative to 100 parts by weight of the positive electrode active material exceeds 10 parts by weight. In this case, it can be confirmed that the resistance increase rate and the capacity retention rate are inferior to those of Examples 1 to 6, and the battery capacity is inferior to that of the battery containing less than 10 parts by weight of the positive electrode active material.

[0124] Comparative Example 4 corresponds to the case where the lithium nickel-based active material is changed to a secondary particle form. In this case, it can be confirmed that in terms of capacity, the results are similar to those of Examples 1 to 6, but the resistance increase rate is about 5% higher than that of Examples 1 to 6, so the effect in terms of capacity retention is poor.

[0125] Comparative Example 5 corresponds to the case where a compound having a nickel content of less than 55 mol% in the lithium nickel-based active material is used. In this case, it can be confirmed that the results are similar to those of Examples 1 to 6 in terms of resistance increase rate and capacity retention rate, but the capacity is significantly lower.

Claims

1. A secondary battery comprising: positive electrode; negative electrode; Diaphragm; and Electrolytes, Wherein, the negative electrode comprises a silicon-based active material and a carbon-based active material, in, The positive electrode comprises: Lithium nickel-based active materials in single particle form, and One or more of LCO (LiCoO2), LMO (LiMn2O4) and LFP (LiFePO4) in the form of secondary particles, and The lithium nickel-based active material in the form of a single particle contains 55 mol % or more of nickel relative to 100 mol % of metals other than lithium.

2. The secondary battery according to claim 1, wherein The content of one or more of LCO (LiCoO2), LMO (LiMn2O4) and LFP (LiFePO4) in the form of secondary particles is 0.1 to 10 parts by weight relative to 100 parts by weight of the positive electrode active material.

3. The secondary battery according to claim 1, wherein The positive electrode has a porosity of 19% to 23%.

4. The secondary battery according to claim 1, wherein The silicon-based active material may be present in an amount of 1 to 15 parts by weight relative to 100 parts by weight of the negative electrode active material.

5. The secondary battery according to claim 1, wherein The average particle size (D 50 ) is 3μm to 10μm.

6. The secondary battery according to claim 1, wherein The positive electrode comprises: Lithium nickel-based active materials in single particle form, and One or more of LMO (LiMn2O4) and LFP (LiFePO4) in the form of secondary particles.

7. The secondary battery according to claim 1, wherein The content of one or more of LCO (LiCoO2), LMO (LiMn2O4) and LFP (LiFePO4) in the form of secondary particles is 0.1 to 3 parts by weight relative to 100 parts by weight of the positive electrode active material.

8. The secondary battery according to claim 1, wherein The lithium nickel-based active material in the form of a single particle contains 55 mol % or more and less than 80 mol % of nickel relative to 100 mol % of metals other than lithium.

9. The secondary battery according to claim 1, wherein The lithium nickel-based active material in the form of a single particle contains 80 mol % or more of nickel relative to 100 mol % of metals other than lithium.

Citation Information

Patent Citations

  • Liquid compositions for inkjet printing of organic layers or other uses

    KR1020120037409A

  • Energy saving monitoring method and apparatus therefor

    KR1020220132117A

  • Data security apparatus

    KR1020230127952A